2020
DOI: 10.1007/s00029-019-0530-7
|View full text |Cite
|
Sign up to set email alerts
|

Moduli spaces of sheaves on K3 surfaces and Galois representations

Abstract: We consider two K3 surfaces defined over an arbitrary field, together with a smooth proper moduli space of stable sheaves on each. When the moduli spaces have the same dimension, we prove that if thé etale cohomology groups (with Q ℓ coefficients) of the two surfaces are isomorphic as Galois representations, then the same is true of the two moduli spaces. In particular, if the field of definition is finite and the K3 surfaces have equal zeta functions, then so do the moduli spaces, even when the moduli spaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In the case of moduli spaces M H (v) of Gieseker-stable sheaves, with Mukai vector v, with respect to a generic polarization H on the K3 surface S (which are special cases of moduli spaces of σ-stable objects in D b (S)), Markman [Mar08,§3.4] has established that there exists an isomorphism between the cohomology algebras of M H (v) and Hilb n (S) that in addition preserves the Hodge structures. Recently, Frei [Fre20] extended Markman's result to positive characteristic, with ℓ-adic cohomology with its Galois structure, in place of singular cohomology with its Hodge structure.…”
Section: The Birational Motive Of Moduli Spaces Of Sheaves On K3 Surf...mentioning
confidence: 99%
“…In the case of moduli spaces M H (v) of Gieseker-stable sheaves, with Mukai vector v, with respect to a generic polarization H on the K3 surface S (which are special cases of moduli spaces of σ-stable objects in D b (S)), Markman [Mar08,§3.4] has established that there exists an isomorphism between the cohomology algebras of M H (v) and Hilb n (S) that in addition preserves the Hodge structures. Recently, Frei [Fre20] extended Markman's result to positive characteristic, with ℓ-adic cohomology with its Galois structure, in place of singular cohomology with its Hodge structure.…”
Section: The Birational Motive Of Moduli Spaces Of Sheaves On K3 Surf...mentioning
confidence: 99%
“…Theorem 3 stands in contrast to a result of Frei [Fre20, Theorem 1], who showed that, over a finite field, two smooth projective moduli spaces of sheaves on a given K3 surface have the same number of points as soon as they have the same dimension.…”
Section: Introductionmentioning
confidence: 76%
“…The usual identification of with the orthogonal to the Mukai vector in the Mukai lattice is valid as -modules; to see this, note that all the maps appearing in [Cha16, Theorem 2.4(vi)] are -equivariant, and see [Fre20, § 2] for the techniques needed to relax condition (C) of [Cha16, Definition 2.3].…”
Section: A Hyperkähler Counterexamplementioning
confidence: 99%
“…In particular Z 1,k and Z 2,k have the same zeta function. In the special case when Z 1 and Z 2 are moduli spaces of stable sheaves on K3 surfaces over k the above statement has already been proven by Frei in [13] via a different method, which uses Markman's results from [19].…”
Section: Introductionmentioning
confidence: 83%